2016
DOI: 10.5209/clac.53477
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between anxiety and academic self-concept in interpreter trainees

Abstract: This paper focuses on two basic issues: the anxiety-generating nature of the interpreting task and the relevance of interpreter trainees' academic self-concept. The first has already been acknowledged, although not extensively researched, in several papers, and the second has only been mentioned briefly in interpreting literature. This study seeks to examine the relationship between the anxiety and academic self-concept constructs among interpreter trainees. An adapted version of the Foreign Language Anxiety S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…The researchers mention such factors as: wish to face a challenge and demonstrate competence, activation of personal interpreting resources, sense of self-efficacy (i.e., the belief in one's capability to carry out a task), as well as maturity and responsibility, since the subjects in this study were the final-year students (Jiménez Ivars & Pinazo Calatayud, 2001: 114-115). The role of the training stage is also visible in the results of Arnaiz-Castro and Pérez-Luzardo Díaz (2016). In their study younger trainees reported higher anxiety levels and had lower self-concept levels.…”
Section: Stress Experienced By Trainee Interpretersmentioning
confidence: 92%
See 2 more Smart Citations
“…The researchers mention such factors as: wish to face a challenge and demonstrate competence, activation of personal interpreting resources, sense of self-efficacy (i.e., the belief in one's capability to carry out a task), as well as maturity and responsibility, since the subjects in this study were the final-year students (Jiménez Ivars & Pinazo Calatayud, 2001: 114-115). The role of the training stage is also visible in the results of Arnaiz-Castro and Pérez-Luzardo Díaz (2016). In their study younger trainees reported higher anxiety levels and had lower self-concept levels.…”
Section: Stress Experienced By Trainee Interpretersmentioning
confidence: 92%
“…With the aid of these tools they measured the correlation between anxiety and academic self-concept in interpreting trainees. The results obtained by Arnaiz-Castro and Pérez-Luzardo Díaz (2016) show that students that exhibited higher anxiety levels tended to have lower self-concept levels.…”
Section: Self-reported Stressmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, because it is sometimes Marcin Walczyński "Will I make it or will I make a fool of myself": Polish-English certified interpreters' experience of anxiety 88 "[…] associated with negative feelings such as uneasiness, frustration, self-doubt, apprehension and tension" (Arnold & Brown, 1999: 8), some scholars equate anxiety with stress (cf. Arnaiz-Castro & Pérez-Luzardo Díaz, 2016). However, at times, stress, the experience of which is partially due to external factors, can intensify the experience of anxiety (cf.…”
Section: Figurementioning
confidence: 99%
“…En referencia a la inseguridad, vergüenza o temor durante el acto comunicativo oral, llegando a ser un impedimento o barrera de índole emocional que impida la comunicación entre interlocutores en la lengua extranjera.8 Horwitz et al (1986) y Arnáiz-Castro et al (2013, 2016a, 2016b enumeran muchas razones y/o factores que desencadenan en ansiedad en los aprendices de LE.…”
unclassified